Investment, Trade, Human Capital, and Economic Growth - Alika, Denisya; Suman, Agus (Journal of Development Economic and Social Studies, 2026)
This study examines the relationship between investment, trade, human capital, and economic growth using regional panel data from Riau Islands Province, Indonesia. Investment, international trade integration, and labor quality are commonly regarded as major drivers of long-term growth, yet their effectiveness often varies across regions. This research employs panel data from seven cities during 2010–2024 and applies the Fixed Effect Model with Moderated Regression Analysis. The results indicate that foreign direct investment and labor does not have a significant direct effect on economic growth, while domestic investment has a negative and significant effect. Trade, proxied by net exports, also shows a negative relationship with growth. Human capital, represented by the Human Development Index, has a negative direct coefficient. However, the interaction between foreign direct investment and human capital is positive and significant, indicating that human capital strengthens the contribution of investment to growth. These findings imply that capital inflows and trade openness alone are insufficient to promote sustainable growth without adequate human capital quality. Policies should therefore integrate investment promotion, trade competitiveness, and human resource development.